MicroRNA as biomarkers of coronary artery disease in real-world practice - V. I. Mikhailina; A. N. Meshkov; A. N. Kiseleva; A. I. Ershova; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The literature review is devoted to circulating microRNA (small noncoding ribonucleic acid molecules) of blood plasma and serum, and potential of their use as new biomarkers of coronary artery disease (CAD) at various stages. The study results demonstrate different levels of plasma and serum microRNA expression in patients with and without CAD. In this regard, determination of microRNA expression level for minimally invasive diagnosis of CAD seems promising, as well as further prognosis of disease progression. A list of microRNAs as potential biomarkers of CAD has been compiled.